Sosialisasi Pemanfaatan Limbah Biomassa Sebagai Bahan Pembuat Briket - Guyup Mahardhian Dwi Putra; Diah Ajeng Setiawati; Asih Priyati; Sirajuddin Haji Abdullah (Jurnal Gema Ngabdi, 2019)
Garbage seems like an unfinished problem in Indonesia, including in Mataram, West Nusa Tenggara. This study aims to reduce organic waste by change it into briquette products that provide benefits value. The method used was distribution of questionnaires, discussions, and practices on how to process organic waste. After this activity, the people become more understands how to treat organic waste and able to use the waste as briquettes